Censorship detected in VE (Venezuela) - Voidly (Voidly Global Censorship Index, 2025)
CRITICAL severity censorship detected in Venezuela. Data sourced from CensoredPlanet.
Censorship Incident ID: VE-2025-0003. Severity: critical. Confidence: 75%